Association of MCP‐1 promoter polymorphism with susceptibility to nasopharyngeal carcinoma. Issue 4 (28th October 2018) - Niu, Yuguang; Zhou, Guangming; Wang, Yahui; Qin, Jianing; Ping, Jie; Zhang, Qing; Han, Bo‐Wei; Liu, Yu‐Xiang; Yang, Chenning; Zhai, Yun; Zhang, Hongxing; He, Fuchu; et al.
Abstract: Nasopharyngeal carcinoma (NPC) is prevalent among populations from southern China and is influenced by both genetic and environmental risk factors. The monocyte chemoattractant protein‐1 (MCP‐1), a member of cysteine‐cysteine chemokine family, plays critical roles in cancers. A polymorphism within the MCP‐1 promoter, rs1024611, has been shown to be significantly associated with the risk of several cancers. Our purpose was to assess the role of rs1024611 in NPC susceptibility. By polymerase chain reaction‐restriction fragment length polymorphism method, we genotyped rs1024611 in 593 patients with NPC (cases) and 480 cancer‐free subjects (controls) among Guangxi population from southern China. We observed that the G allele of rs1024611 was significantly associated with the increased risk of NPC in an additive model and dominant model, respectively ( P  = 0.018 and 0.010, odds ratio = 1.25 and 1.41, respectively). No appreciable variation of the effects was found across the subgroups stratified by age, sex, nationality, smoking and drinking status, and smoking level. In addition, significantly higher messenger RNA (mRNA) expression level of MCP‐1 was observed in NPC tissues than that in normal nasopharyngeal tissues, and the G allele of rs1024611 was significantly associated with elevated mRNA expression level of MCP‐1 in Epstein‐Barr virus‐transformed lymphocytes. In conclusion, our findings suggested that rs1024611 at the MCP‐1 promoter may be a risk factor for NPC. Further studies with larger sample size are necessary to confirm these findings. Abstract : By polymerase chain reaction‐restriction fragment length polymorphism (PCR‐RFLP) method, we genotyped rs1024611 in 593 patients with nasopharyngeal carcinoma (NPC) (cases) and 480 cancer‐free subjects (controls) among Guangxi population from southern China. We observed that the G allele of rs1024611 was significantly associated with the increased risk of NPC in an additive model and dominant model, respectively ( P  = 0.018 and 0.010, odds ratio [OR] = 1.25 and 1.41, respectively). In addition, significantly higher messenger RNA (mRNA) expression level of monocyte chemoattractant protein‐1 (MCP‐1) was observed in NPC tissues than that in normal nasopharyngeal tissues, and the G allele of rs1024611 was significantly associated with elevated mRNA expression level of MCP‐1 in Epstein‐Barr virus (EBV)‐transformed lymphocytes.